Auxiliary Kirschner wire technique in the closed reduction of children with Gartland Type III Supracondylar humerus fractures. Issue 34 (August 2019) - Dong, Liangchao; Wang, Yichen; Qi, Muyu; Wang, Sun; Ying, Hao; Shen, Yang
Abstract : Abstract: This study aimed to investigate the effect of auxiliary Kirschner wire (K-wire) technique in the closed reduction of children with Gartland type III supracondylar humerus fractures by comparing with manual reduction alone. Retrospective analysis was performed on the clinical data of 68 cases of supracondylar humerus fractures. Thirty-six patients received closed reduction and percutaneous fixation with auxiliary K-wire technique (group A). Thirty-two patients received conventional manual reduction and percutaneous pin fixation (Group B). In group A, the average operation time was 20.5 ± 8.5 minutes, the average frequency of intraoperative radiographic observations was 4.3 ± 1.1, the average fracture healing time was 6.2 ± 1.8 weeks, and the complication rate was 3/36, 8.3%. The mean operation time was 36.1 ± 10.2 minutes, the average frequency of intraoperative radiography was 8.9 + 1.7 times, the average fracture healing time was (6.1 ± 1.6) weeks, and the complication rate was 2/32, 6.3%. The operation time in group A was significantly shorter than that in group B. The difference between the 2 groups was statistically significant ( P  = .012). The frequency of radiography in group A was significantly less than that in group B ( P  = .001). Compared with manual reduction, auxiliary K-wire technology can significantly shorten the operation time, reduce the radiant quantity of the surgeon, improve the efficiency of closed reduction of children with Gartland type III supracondylar humerus fractures, and reduce the risk of developing postoperative complications. And meanwhile, there is no significant effect on the imaging and functional outcomes of affected extremities, which is worthy of respect.